Modified polyphenyl ether resin, preparation method thereof and resin composition containing modified polyphenyl ether resin

By modifying the polyshenol resin, reacting with polyphenol compounds and free radical initiators, alkali washing and solvent recrystallization, the mass and quantity problems of existing resins when manufacturing copper foil substrates are solved. , achieving higher quality and more flexible copper foil substrate manufacturing.

CN119431770APending Publication Date: 2025-02-14NANYA PLASTICS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311181776.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-31
Filing Date
2023-09-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When manufacturing copper foil substrates, the existing polystyrene alcohol resin has a large molecular weight and high viscosity, which leads to a low quality and quantity ratio of the copper foil substrate, and it is difficult to customize and adjust according to different needs.

Method used

The modified polyphenylene ether resin was prepared by reacting the unmodified polyphenylene ether with a polyphenol compound and a free radical initiator, and alkali washing and solvent recrystallization. This method adjusts the molecular weight and distribution of the resin to make it more suitable for the manufacture of electronic components.

Benefits of technology

The modified polyphenylene ether resin is relatively simple in preparation, suitable for electronic components or electronic products, and the copper foil substrate produced has good quality and can meet the specification adjustments of different needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431770A_ABST
    Figure CN119431770A_ABST
Patent Text Reader

Abstract

The invention provides modified polyphenyl ether resin. The modified polyphenyl ether resin has a structure as shown in a formula 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified resin and a preparation method thereof, in particular to a modified polyphenylene ether resin and a preparation method thereof. Background Art

[0002] With the popularization of the fifth generation mobile networks (5G), the printed circuit board (PCB) industry is shifting towards higher speed and higher frequency circuit boards, which has also promoted the continuous development and improvement of copper clad laminate (CCL) materials. Copper clad laminates are usually composed of copper foil, glass fiber cloth and resin, among which polyphenylene ether resin is a commonly used insulating material. However, the molecular weight of general industrial-grade polyphenylene ether may be larger and the viscosity may be higher, which may result in the quality and / or yield of the produced copper clad laminate being lower. In addition, its corresponding specifications are more difficult to customize according to different needs. Therefore, how to modify polyphenylene ether resin (such as: terminal functional group modification, molecular weight and its distribution corresponding adjustment) to make the production of copper clad laminates easier and / or to make the manufactured copper clad laminates still have good quality has become a current research topic. Summary of the invention

[0003] The invention provides a modified polyphenylene ether resin and a preparation method thereof, and a resin composition containing the modified polyphenylene ether resin.

[0004] According to an embodiment of the present invention, a method for preparing a modified polyphenylene ether resin comprises the following steps: providing unmodified polyphenylene ether; reacting the unmodified polyphenylene ether with a polyphenol compound and a free radical initiator to obtain a corresponding product; and alkali washing and solvent recrystallization of the product to obtain a modified polyphenylene ether resin.

[0005] According to an embodiment of the present invention, the modified polyphenylene ether resin has a structure as represented by [Formula 1] in the specification.

[0006] According to an embodiment of the present invention, the resin composition includes the aforementioned modified polyphenylene ether resin.

[0007] According to an embodiment of the present invention, an electronic component includes a film layer formed by the aforementioned resin composition.

[0008] Based on the above, the modified polyphenylene ether resin of the present invention can be prepared relatively simply and can be applied to electronic components or electronic products (such as circuit boards or copper foil substrates). BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1It is a schematic flow chart of a method for preparing a modified polyphenylene ether resin according to an embodiment of the present invention.

[0010] Description of Reference Numerals

[0011] S10, S20, S30, S40: Steps DETAILED DESCRIPTION

[0012] In the following detailed description, for the purpose of illustration and not limitation, exemplary embodiments that disclose specific details are set forth to provide a thorough understanding of the various principles of the present invention. However, it will be apparent to one of ordinary skill in the art that, with the benefit of this disclosure, the present invention may be practiced in other embodiments that depart from the specific details disclosed herein. In addition, descriptions of well-known devices, methods, and materials may be omitted to avoid obscuring the description of the various principles of the present invention.

[0013] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may also be expressed directly as one particular value and / or to another particular value. When expressing the range, another embodiment includes from the one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about," it will be understood that the particular value forms another embodiment. For example, when a value is expressed using the antecedent "about," it may be expressed directly as the particular value. Also, when the value is expressed using the antecedent "about," it may be in the range of ±3% of the value; further, in the range of ±1% of the value. It will be further understood that the endpoints of each range are clearly related to or independent of the other endpoint.

[0014] In this document, non-limiting terms (such as: may, can, for example or other similar terms) mean that implementation, inclusion, addition or existence are optional or necessary.

[0015] In this context, a derivative of a compound may be a non-reactive hydrogen atom in the compound which may be substituted with an isotope or with a non-reactive alkyl group of one to five carbon atoms (calculated as: C1-C5).

[0016] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.

[0017] Please refer to Figure 1The preparation method of modified polyphenylene ether resin may include the following steps. Step S10: providing unmodified polyphenylene ether. Step S20: modifying the aforementioned polyphenylene ether by reacting with a polyphenol compound and a free radical initiator. Step S30: purifying the product after the aforementioned reaction by alkali washing and solvent recrystallization. Step S40: obtaining modified polyphenylene ether.

[0018] <Modification of polyphenylene ether resin>

[0019] In one embodiment, the corresponding modification can be performed by appropriately reacting unmodified polyphenylene ether, polyphenolic compounds, and free radical initiators to obtain or generate corresponding products.

[0020] In one embodiment, the unmodified polyphenylene ether may be a polyphenylene ether having only hydrogen or an alkyl group of one to five carbon atoms (which can be calculated as: C1-C5) substituted on the corresponding phenyl group. For example, the unmodified polyphenylene ether may be poly(2,6-dimethyl-1,4-phenylene ether) (CAS No.: 25134-01-4), but the present invention is not limited thereto.

[0021] In one embodiment, the polyphenol compound includes, for example, a bisphenol compound. In one embodiment, the bisphenol compound includes, for example, bisphenol A (BPA), tetramethyl bisphenol F (TMBP), tetramethyl bisphenol A (TMBPA), tetramethyl bisphenol F (TMBPF), bisphenol S (BPS), dicyclopentadiene bisphenol (e.g., DCPD-DIDMP), or derivatives thereof.

[0022] In one embodiment, the polyphenolic compound includes, for example, a tetraphenolic compound. In one embodiment, the tetraphenolic compound includes, for example, 1,1,2,2-tetrakis(p-hydroxyphenyl)ethane (TPE, CAS No.: 7727-33-5) or its derivatives.

[0023] In one embodiment, the free radical initiator includes, for example, a peroxide; preferably, the free radical initiator can be a peroxide without a corresponding benzene ring. In one embodiment, the free radical initiator can include benzoyl peroxide (BPO) or its derivatives (e.g., alkyl-substituted benzoyl peroxide). The "alkyl substitution" mentioned above or below can be a substitution of at least one hydrogen with an alkyl group of one to five carbon atoms (which can be calculated as: C1-C5).

[0024] In one embodiment, the reaction with unmodified polyphenylene ether, polyphenolic compound, and free radical initiator as products can be similar to a rearrangement reaction. The reaction mechanism may be that the free radical initiator forms free radicals by an appropriate method (such as heating). Then, the aforementioned free radicals can attack the end of the polyphenolic compound to form corresponding free radicals; and / or, the aforementioned free radicals can attack the end of the polyphenylene ether to form corresponding free radicals. The polyphenylene ether with terminal free radicals and the polyphenolic compound with terminal free radicals can terminate the reaction by reacting / combining with each other's free radicals, and generate corresponding molecules / polymers with at least two hydroxyl groups. In addition, the aforementioned free radicals can also react with the benzene ring and / or the structure thereon of the polyphenylene ether, which may reduce the chain length of the polyphenylene ether and correspondingly reduce the molecular weight of the polyphenylene ether. Therefore, in the aforementioned reaction, the reaction amount relationship between the polyphenylene ether and the free radical initiator may be related to the molecular weight or polydispersity index (PDI) of the product. For example, if the ratio of free radical initiator is higher (e.g., higher molar number), the molecular weight of the product may be lower and / or the polydispersity index may be higher. Conversely, if the ratio of free radical initiator is lower (e.g., lower molar number), the molecular weight of the product may be higher and / or the polydispersity index may be lower. The polydispersity index (PDI), which may also be referred to as molecular weight distribution, is the weight average molecular weight divided by the number average molecular weight (i.e., Mw / Mn).

[0025] In one embodiment, the equivalent of the free radical initiator is about 0.05 to about 2 times the phenol equivalent of the polyphenol compound. In other words, the phenol equivalent of the polyphenol compound: the equivalent of the free radical initiator ≒ 100:5 to 100:200. In this way, the average number of hydroxyl groups contained in each modified polyphenylene ether molecule after the reaction can be greater than about 2.0.

[0026] In one embodiment, preferably, the equivalent of the free radical initiator is about 0.1 to about 1.5 times the phenol equivalent of the polyphenolic compound, that is, the phenol equivalent of the polyphenolic compound: the equivalent of the free radical initiator ≒100:10 to 100:150.

[0027] In one embodiment, preferably, the equivalent weight of the free radical initiator can be less than the phenol equivalent weight of the polyphenolic compound. In this way, the possibility of side reactions can be reduced (but it does not mean that it can be completely avoided under the natural conditions of chemical reactions).

[0028] In one embodiment, more preferably, the phenol equivalent of the polyphenolic compound is about 1.5 times to about 20 times the equivalent of the free radical initiator. In one embodiment, more preferably, the phenol equivalent of the polyphenolic compound is greater than 1.5 times (e.g., about 1.75 times, about 1.8 times, or about 2 times) to about 10 times the equivalent of the free radical initiator.

[0029] In one embodiment, a catalyst may be added (but not limited to). The catalyst may increase the reaction rate of the rearrangement reaction. The catalyst may be added together with the polyphenolic compound. The catalyst may include a water-soluble catalyst, such as a tertiary amine, a quaternary amine salt, a phosphate salt, or a combination thereof that is suitable for being soluble in water. For example, the catalyst may include tetraalkylammonium halides (e.g., tetramethylammonium chloride (TMAC, CAS No. 75-57-0), tetraethylammonium chloride (TEAC, CAS No. 56-34-8), tetramethylammonium bromide (TMAB, CAS No. 64-20-0), tetraethylammonium bromide (TEAB, CAS No. 71-91-0), tetrapropylammonium bromide (TPAB, CAS No. 1941-30-6), tetrabutylammonium bromide (TBAB, CAS No. 1643-19-2)), benzylalkylammonium halides (e.g., benzyltrimethylammonium chloride (TBAB, CAS No. 1643-19-2)), chloride (BTMAC, CAS No.: 56-93-9), benzyltriethylammonium chloride (BTEAC, CAS No.: 56-37-1) or N-decyl-N,N-dimethylbenzyl ammonium chloride (benzyldimethyldecylammonium chloride, CAS No.: 965-32-2). In one embodiment, the added weight of the catalyst can be about 1wt% or less of the weight of the unmodified polyphenylene ether used in the reaction, based on the weight of the unmodified polyphenylene ether used in the reaction.

[0030] In one embodiment, the average number of hydroxyl groups contained in each modified polyphenylene ether molecule can be estimated by dividing the total molar number of hydroxyl groups by the total molar number of modified polyphenylene ether molecules (i.e., the total molar number of hydroxyl groups÷the total molar number of modified polyphenylene ether molecules). The total molar number of hydroxyl groups can be calibrated by the commonly used standards (such as, but not limited to, ISO 4629-2:2016, ASTMD1959, GB / T 12008.3, CNS 6681). The total molar number of polymer molecules can be converted by measuring the corresponding average molecular weight by gel permeation chromatography (GPC).

[0031] In one embodiment, the modification reaction can be carried out in a hydrophobic solvent or a lipophilic solvent. In one embodiment, the modification reaction can be carried out in toluene, xylene or the aforementioned co-solvent.

[0032] In one embodiment, the aforementioned modification reaction can be performed in an environment with a temperature greater than room temperature (eg, greater than 25° C.). In one embodiment, the modification reaction can be performed in an environment with a temperature greater than or equal to about 80° C.

[0033] In one embodiment, the aforementioned modification reaction may be performed in an environment with a temperature lower than the boiling point of the corresponding solvent.

[0034] In one embodiment, the aforementioned modification reaction can be carried out for about 0.5 hours to 6 hours. In one embodiment, the aforementioned modification reaction can be carried out for about 1 hour to 5 hours. In one embodiment, the aforementioned modification reaction can be carried out for about 2 hours to 4 hours. In one embodiment, the aforementioned modification reaction can be carried out for about 3 hours.

[0035] In one embodiment, the modified polyphenylene ether after the reaction can be subjected to alkali washing. In this way, the phenol equivalent of the modified polyphenylene ether can be further increased. In one embodiment, after the modified polyphenylene ether after the reaction is subjected to alkali washing, the average number of hydroxyl groups contained in each modified polyphenylene ether molecule can be greater than 2.2.

[0036] In one embodiment, the aforementioned alkali washing can be performed by a corresponding alkali solution. In one embodiment, the alkali solution may include a solution containing alkali gold ions or alkaline earth gold ions; preferably, it is a solution containing alkali gold ions. Cations with a valence greater than or equal to +3 may cause unnecessary side reactions. For example, the alkali solution may include sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, sodium alcoholate (such as sodium methoxide (MeONa), sodium ethoxide (EtONa), sodium propoxide, sodium butoxide), potassium alcoholate (such as potassium methoxide (MeOK), potassium ethoxide (EtOK), potassium propoxide, potassium butoxide) or a mixed solution thereof dissolved in a suitable solvent (such as water, alcohol, or a mixture of alcohol and water).

[0037] In one embodiment, the alkali solution used for alkali washing may have an alkali equivalent of about 10 wt % to about 60 wt % of a sodium hydroxide aqueous solution.

[0038] In one embodiment, the alkaline washing process can be carried out in an environment with a temperature greater than room temperature (eg, greater than 25° C.) In one embodiment, the alkaline washing process can be carried out in an environment with a temperature greater than or equal to about 40° C.

[0039] In one embodiment, the aforementioned alkaline washing process may be performed in an environment with a temperature lower than the boiling point of the corresponding solvent.

[0040] In one embodiment, the alkali washing process can be carried out for about 0.5 hours to 4 hours. In one embodiment, the modification reaction can be carried out for about 0.5 hours to 3 hours. In one embodiment, the modification reaction can be carried out for about 1 hour to 2 hours.

[0041] In one embodiment, after the aforementioned modified polyphenylene ether molecules are formed, unreacted or unreacted macromolecular polyphenylene ethers can be removed by solvent purification and / or recrystallization. For example, compared to modified polyphenylene ether molecules with a molecular weight of about 20,000 mole / g, unreacted or unreacted macromolecular polyphenylene ethers with a molecular weight of more than 40,000 may have a lower solubility in certain low-polarity solvents (such as tetrahydrofuran, butanone, methyl isobutyl ketone, cyclohexanone). Therefore, unreacted or unreacted macromolecular polyphenylene ethers can be precipitated and removed by adding the aforementioned low-polarity solvent. In addition, a corresponding high-polarity solvent (such as methanol, ethanol or isopropanol) can be added to recrystallize and precipitate the modified polyphenylene ether. In this way, the purity and / or quality of the modified polyphenylene ether can be improved.

[0042] In one embodiment, the above-mentioned solvent purification method and recrystallization can obtain a modified polyphenylene ether having a number-average molecular weight (Mn) of about 500 g / mol to 4,000 g / mol, and a polydispersity index (PDI) of less than or equal to about 2.5.

[0043] In one embodiment, the above-mentioned solvent purification method and recrystallization can preferably obtain a modified polyphenylene ether having a number-average molecular weight (Mn) of about 1,000 g / mol to 3,000 g / mol, and a polydispersity index (PDI) of less than or equal to about 1.8.

[0044] In one embodiment, the solvent used for recrystallization may include toluene, xylene, tetrahydrofuran (THF), methyl ethyl ketone (MEK), cyclohexanone, methyl isobutyl ketone (MIBK), or a co-solvent thereof.

[0045] In one embodiment, the modified polyphenylene ether may be as shown in the following [Formula 1].

[0046] [Formula 1]

[0047]

[0048] In [Formula 1], k is an integer greater than or equal to 0; i, i', j, j' may be the same or different; i and j may be integers of 0 to 200; and i' and j' may be integers of 1 to 200. Furthermore, the value of i+i'+j+j'+k may be between 2 and 400.

[0049] In [Formula 1], preferably, k is 0 or 1; i, i', j, j' may be the same or different, and each may be an integer of 1 to 200. Furthermore, the value of i+i'+j+j'+k may be between 4 and 200.

[0050] In [Formula 1], R1 to R8 may be the same or different, and may be selected from hydrogen or an alkyl group having one to six carbon atoms (represented as: C1 to C6).

[0051] In [Formula 1], P1 to P4 may be the same or different from each other, and each may be selected from a single bond (-) or a ketone group (-). ).

[0052] In [Formula 1], Q1 to Q4 may be the same or different, and each may be selected from a phenyl group, a phenylvinyl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methylvinyl group, a naphthyl group or hydrogen.

[0053] In [Formula 1], X may be a single bond (-) or a linking group selected from the following:

[0054] In one embodiment, after the aforementioned solvent purification method and recrystallization, the proportion of macromolecular polyphenylene ether with a molecular weight of more than 20,000 g / mole can be substantially less than 1.5 wt % based on the total weight of the dried product; preferably, less than about 1.0 wt %.

[0055] In one embodiment, the number-average molecular weight (Mn) of the modified polyphenylene ether resin may be about 500 g / mol to 4,000 g / mol; preferably, about 1,000 g / mol to 3,000 g / mol.

[0056] In one embodiment, the polydispersity index of the modified polyphenylene ether resin is less than or equal to about 2.5; preferably, less than or equal to about 1.8.

[0057] In one embodiment, the hydroxyl equivalent of the modified polyphenylene ether resin is less than or equal to about 1,300 g / eq, and the number of hydroxyl groups per molecule is about 2.0-4.0.

[0058] <Application of modified polyphenylene ether resin>

[0059] The modified polyphenylene ether resin represented by [Formula 1] can be suitable for application in electronic products.

[0060] Since the modified polyphenylene ether resin shown in [Formula 1] can have lower dielectric properties, higher glass transition temperature (glass transition temperature, Tg), better heat resistance and / or better fluidity, it can be suitable for application in electronic products.

[0061] Since the modified polyphenylene ether resin shown in [Formula 1] can be easily dissolved in commonly used organic solvents (such as toluene or methyl ethyl ketone (MEK), it is relatively convenient to use.

[0062] In one embodiment, the modified polyphenylene ether resin shown in [Formula 1] can have better heat resistance, higher glass transition temperature and / or better fluidity in the application of electronic products compared with other conventional resins that can be used in electronic products.

[0063] In one embodiment, the modified polyphenylene ether resin shown in [Formula 1] may have better heat resistance, higher glass transition temperature and better fluidity in the application of electronic products compared with other conventional resins that can be used in electronic products. As a result, its application (such as application in copper foil substrate) can be simpler.

[0064] In one embodiment, the resin composition may include the modified polyphenylene ether resin of the aforementioned embodiment. In one embodiment, based on 100 parts by weight of the total weight of the resin composition, the modified polyphenylene ether resin may be 30 parts by weight (wt%) to 60 parts by weight; preferably, about 40 parts by weight.

[0065] In one embodiment, the resin composition may further include a crosslinking agent. In one embodiment, based on 100 parts by weight of the total weight of the resin composition, the crosslinking agent may be 10 parts by weight to 20 parts by weight, preferably about 15 parts by weight.

[0066] In one embodiment, the addition of a crosslinking agent can enhance the degree of crosslinking between the resin and / or the corresponding polymer. In one embodiment, the crosslinking agent may include an allyl group. In one embodiment, the crosslinking agent may include triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethallyl isocyanurate (TMAIC), diallyl phthalate, divinylbenzene, triallyltrimellitate, or a combination thereof.

[0067] In one embodiment, the resin composition may further include a filler. In one embodiment, based on 100 parts by weight of the total weight of the resin composition, the filler may be 5 parts by weight to 15 parts by weight, preferably about 10 parts by weight.

[0068] In one embodiment, the addition of an inorganic filler can increase the viscosity of the resin composition. For example, the inorganic filler can be silicon dioxide, titanium dioxide, aluminum hydroxide, aluminum oxide, magnesium hydroxide, magnesium oxide, calcium carbonate, boron oxide, calcium oxide, strontium titanate, barium titanate, calcium titanate, magnesium titanate, boron nitride, aluminum nitride, silicon carbide, cerium dioxide, or a combination thereof.

[0069] In one embodiment, the silicon dioxide added as an inorganic filler may include molten silicon dioxide or crystalline silicon dioxide. In one embodiment, considering the dielectric properties when applied to a copper foil substrate, molten silicon dioxide is more preferred.

[0070] In one embodiment, the titanium dioxide added as an inorganic filler may include titanium dioxide in rutile, anatase or brookite configurations. In one embodiment, considering the dielectric properties when applied to a copper foil substrate, titanium dioxide in rutile configuration is more preferred.

[0071] In one embodiment, the resin composition may further include a cross-linking accelerator. In one embodiment, based on 100 parts by weight of the total weight of the resin composition, the cross-linking accelerator may be 0.5 parts by weight to 1.5 parts by weight, preferably about 1.0 parts by weight.

[0072] In one embodiment, a cross-linking accelerator can enhance the reactivity of the system. The accelerator can include a catalyst and a peroxide.

[0073] In one embodiment, the catalyst used as the cross-linking accelerator may include 1-cyanoethyl-2-phenylimidazole (2PZCN; CAS: 23996-12-5), 1-benzyl-2-phenylimidazole (1B2PZ; CAS: 37734-89-7), thiabendazole (TBZ; CAS: 148-79-8), or a combination thereof, but the present invention is not limited thereto.

[0074] In one embodiment, the peroxide used as the crosslinking accelerator may include tert-butyl isopropyl peroxide, dicumyl peroxide (DCP), benzoyl peroxide (BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, 1,1-di-(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di(tert-butylperoxyisopropyl)benzene, F series peroxide formula (such as: 1,3 (4) -Bis (tert-butylperoxyisopropyl) benzene, LuF) or a combination thereof, but the present invention is not limited thereto.

[0075] In one embodiment, the resin composition may further include a flame retardant. In one embodiment, based on 100 parts by weight of the total weight of the resin composition, the flame retardant may be 5 parts by weight to 15 parts by weight, preferably about 10 parts by weight.

[0076] In one embodiment, the addition of flame retardant can improve the flame retardancy or flame retardancy of the resin composition. In this article, "flame retardant" or "flame retardant" means that the object (such as a film, layer or structure) can pass the flame retardancy standard of the standard test method. For example, the UL94 plastic flammability standard (Test for Flammability of Plastic Materials for Parts in Devices and Appliances) issued by Underwriters Laboratories Inc (UL) is at least HB grade.

[0077] In one embodiment, the flame retardant may include a bromine-based flame retardant, a phosphorus-based flame retardant, or a combination thereof, but the present invention is not limited thereto.

[0078] In one embodiment, the brominated flame retardant includes Saytex BT 93W (ethylene bistetrabromophthalimide) flame retardant, Saytex BT93, Saytex 120 (tetradecabromodiphenoxy benzene) flame retardant, Saytex 8010 (Ethane-1,2-bis (pentabromophenyl)) flame retardant, Saytex 102 (decabromo diphenoxy oxide) flame retardant or a combination thereof produced by Albemarle Corporation of the United States.

[0079] In one embodiment, the phosphorus flame retardant may include sulphosuccinic acid ester, phosphazene, ammonium polyphosphate, melamine polyphosphate, melamine cyanurate, or a combination thereof. For example, it may include triphenyl phosphate (TPP), resorcinol bis (diphenylphosphate), bisphenol A bis (diphenyl phosphate), BPAPP, resorcinol diphosphate (such as CR-733S produced by Daihachi Chemical Co., Ltd.), resorcinol-bis (di-2,6-dimethylphenyl phosphate) (such as PX-200 produced by Daihachi Chemical Co., Ltd.), Otsuka Chemical SPB-100 phosphorus flame retardant, or a combination thereof.

[0080] In one embodiment, a resin composition containing the modified polyphenylene ether resin according to one embodiment of the present invention can be used to manufacture electronic components (such as, but not limited to, copper foil substrates or printed circuit boards).

[0081] In one embodiment, a resin composition containing a modified polyphenylene ether resin according to one embodiment of the present invention can be suitable for forming an insulating film of an electronic product, and when used in an electronic product, it can have the following specifications: a dielectric constant (Dk) of less than or equal to about 4.0 (e.g., about 3.3 to 4.0); a dielectric loss (Df) of less than or equal to about 0.0050 (e.g., about 0.0035 to 0.0050); a glass transition temperature (Tg) of about 210°C to 235°C; a peel strength greater than about 6.0 lb / in (e.g., can be further greater than or equal to 6.5 lb / in); and / or a water absorption rate less than or equal to about 0.5% (e.g., a 2hr water absorption rate less than or equal to about 0.5%).

[0082] Most of the commercially available resins used in the manufacture of copper foil substrates (such as the resin model SA-9000 prepared by Sabic Company, but not limited to) are prepared by oxidative polymerization. However, the aforementioned oxidative polymerization method requires the introduction of oxygen. In the process of introducing oxygen, the flow rate, flow velocity and / or concentration of oxygen must be controlled to avoid the possibility of increasing violent oxidation reactions (such as combustion, flash fire or explosion) due to the coexistence of solvent and oxygen. In addition, the reaction tank suitable for the aforementioned oxidative polymerization method must have corresponding gas detectors, fire prevention equipment and / or explosion-proof equipment, so the corresponding reaction cost is higher. In addition, the aforementioned oxidative polymerization method often requires the addition of metal catalysts (mostly metals with a valence of more than +3 or transition metals), and the metal catalysts often need to be purified before they can be separated from the product, so the corresponding reaction steps are more complicated. Furthermore, the aforementioned oxidative polymerization method often needs to be carried out in a specific environment (such as a specific solvent), and its properties are more difficult to customize. Based on the above, compared with the commercially available resin for manufacturing copper foil substrates, the modified polyphenylene ether resin of one embodiment of the present invention can be prepared more simply. In addition, the modified polyphenylene ether resin of one embodiment of the present invention can be applied to the manufacture of copper foil substrates, and / or the copper foil substrates manufactured using the modified polyphenylene ether resin can meet the commonly used specifications.

[0083] <Manufacturing of Copper Foil Substrate>

[0084] The modified polyphenylene ether resin of the above embodiment can be dissolved in a suitable solvent and mixed with other components to form a resin varnish, and a copper foil substrate can be prepared by a conventional method. For example, the resin composition of the above embodiment can be dissolved in a suitable solvent to form a resin varnish, and can be used to manufacture a copper foil substrate.

[0085] A method for manufacturing a copper foil substrate may be as follows.

[0086] The 2116 fiberglass cloth is impregnated with the resin varnish and then dried for several minutes at about 170°C (impregnation machine temperature). The drying time is adjusted to control the melt viscosity of the dried prepreg to be between about 4,000 and 12,000 poise. Then, four prepregs are stacked between two copper foils of about 35 μm thickness and pressed (described in detail below) to form a copper foil substrate of an embodiment.

[0087] The conditions / process of the pressing step are exemplified as follows:

[0088] Step 1: Raise the temperature from about 80°C to about 195°C at a rate of about 0.5 hours (recorded as: 85↗195°C, 0.5hr).

[0089] Step 2: Reduce the pressure from about 7 kg / cm 2 Increase to about 25kg / cm 2 (It can be recorded as: 7↗25kg / cm 2 , 0.5hr)

[0090] Step 3: At a temperature of about 195°C and a pressure of about 25 kg / cm 2 Press for about 2.0 hours (can be recorded as: 195℃ / 25kg / cm 2 , 2.0hr).

[0091] <Examples and Comparative Examples>

[0092] The following examples and comparative examples are presented to illustrate the present invention in detail, but the present invention is not limited to the following examples at all. It is worth noting that, for the sake of brevity, some numerical values ​​in the examples or comparative examples (such as the numerical values ​​recorded in the table) may omit the expression of "about". Each numerical value may include the value and the average value within the acceptable deviation range of the specific value determined by a person of ordinary skill in the art, taking into account the measurement in question and the specific number of errors associated with the measurement (i.e., the limitations of the measurement system) and having a range of ±3% of the value; further, a range of ±1% of the value.

[0093] <Preparation Example of Modified Polyphenylene Ether Resin and Corresponding Comparative Example>

[0094] <Example 1>

[0095] About 600 g of toluene and about 100 g of commercially available polyphenylene ether (trade name: XYRON TM S203A, manufactured by Asahi Kasei Engineering Plastics), about 0.5 g of tetramethylammonium chloride and about 8.25 g of tetramethylbisphenol A, and heated to 90° C. to dissolve.

[0096] Then, about 3.7 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least four times) over a period of about 60 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 90° C.).

[0097] After the above-mentioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 90° C.) for about 3 hours.

[0098] After the reaction, the reaction solution is alkali washed with an appropriate amount of 20 wt % sodium hydroxide aqueous solution (e.g., the total volume ratio of the reaction solution to the sodium hydroxide aqueous solution used may be about 1:1 to 1:5) at a constant temperature (about 70° C.) for about 1 hour. Thereafter, the water layer is removed.

[0099] Then, tetrahydrofuran is added to the organic solvent layer after the water layer is removed to recrystallize and remove the unreacted or unreacted polyphenylene ether at about 15° C. or below. Thereafter, methanol is added to precipitate the resin and dry it.

[0100] The number average molecular weight of the resin of Example 1 may be about 2,772 g / mole, the molecular weight distribution may be about 1.47, the resin hydroxyl equivalent may be about 1260 g / eq, and the number of hydroxyl groups per molecule (i.e., number average molecular weight / resin hydroxyl equivalent) may be about 2.2. Furthermore, the total weight of polymer single molecules with a molecular weight of more than 20,000 g / mole accounts for about 0.5 wt% of the total weight of the resin.

[0101] <Example 2>

[0102] About 600 g of toluene and about 100 g of commercially available polyphenylene ether (trade name: XYRON TM S202A, manufactured by Asahi Kasei Engineering Plastics), about 0.5 g of benzyltrimethylammonium chloride and about 11.6 g of tetramethylbiphenol, and heated to about 100° C. to dissolve.

[0103] Then, about 5.2 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least eight times) over a period of about 120 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 100° C.).

[0104] After the aforementioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 100° C.) for about 3 hours.

[0105] After the reaction, the reaction solution is alkali washed with an appropriate amount of sodium methoxide at a constant temperature (about 50° C. or above, such as about 50° C. to 70° C.) for about 1 hour. Thereafter, water is added for washing, and then the water layer is removed.

[0106] Then, methyl ethyl ketone is added to the organic solvent layer after the water layer is removed to recrystallize and remove the unreacted or unreacted polyphenylene ether at about 15° C. or below. Thereafter, methanol is added to precipitate the resin and dry it.

[0107] The number average molecular weight of the resin of Example 2 may be about 2,320 g / mole, the molecular weight distribution may be about 1.43, the resin hydroxyl equivalent may be about 960 g / eq, and the number of hydroxyl groups per molecule may be about 2.4. Furthermore, the total weight of the polymer single molecule with a molecular weight of more than 20,000 g / mole accounts for about 0.3 wt% of the total weight of the resin.

[0108] <Example 3>

[0109] About 600 g of xylene and about 100 g of commercially available polyphenylene ether (trade name LXR-035, manufactured by China National Bluestar (Group) Co., Ltd.) and about 20 grams of 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, and heated to about 110° C. to dissolve.

[0110] Then, about 10 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least twelve times) over a period of about 240 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 110° C.).

[0111] After the above-mentioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 110° C.) for about 3 hours.

[0112] After the reaction, the reaction solution is subjected to alkaline washing with an appropriate amount of sodium methoxide at a constant temperature (about 50° C. or above, such as about 50° C. to 70° C.) for about 2 hours. Thereafter, water is added for washing, and then the water layer is removed.

[0113] Then, cyclohexanone is added to the organic solvent layer after the water layer is removed to recrystallize and remove the unreacted or unreacted polyphenylene ether at about 4° C. or below. Thereafter, methanol is added to precipitate the resin and dry it.

[0114] The number average molecular weight of the resin of <Example 3> can be about 2,124 g / mole, the molecular weight distribution can be about 1.50, the resin hydroxyl equivalent can be about 566 g / eq, and the number of hydroxyl groups per molecule can be about 3.75. In addition, the total weight of the polymer single molecule with a molecular weight of more than 20,000 g / mole accounts for about 0.9 wt% of the total weight of the resin.

[0115] <Example 4>

[0116] About 600 g of toluene and about 100 g of commercially available polyphenylene ether (trade name: XYRON TM S203A), about 0.5 grams of tetramethylammonium chloride and about 19 grams of tetramethylbiphenol, and heated to 90°C to dissolve.

[0117] Then, about 6 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least six times) over a period of about 120 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 90° C.).

[0118] After the above-mentioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 90° C.) for about 3 hours.

[0119] After the reaction, the reaction solution was subjected to alkaline washing with an appropriate amount of 8 wt % sodium bicarbonate aqueous solution at a constant temperature (about 70° C.) for about 1 hour. Thereafter, the water layer was removed.

[0120] Then, methyl isobutyl ketone is added to the organic solvent layer after the water layer is removed to recrystallize and remove the unreacted or unreacted polyphenylene ether at about 25° C. or below. Thereafter, methanol is added to precipitate the resin and dry it.

[0121] The number average molecular weight of the resin of Example 4 may be about 1,750 g / mole, the molecular weight distribution may be about 1.60, the resin hydroxyl equivalent may be about 670 g / eq, and the number of hydroxyl groups per molecule may be about 2.60. Furthermore, the total weight of the polymer single molecule with a molecular weight of more than 20,000 g / mole accounts for about 0.1 wt% of the total weight of the resin.

[0122] <Example 5>

[0123] About 600 g of toluene and about 100 g of commercially available polyphenylene ether (trade name: XYRON TM S202A), about 0.5 grams of tetramethylammonium chloride and about 42 grams of tetramethylbiphenol, and heated to about 80°C to dissolve.

[0124] Then, about 10 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least six times) over a period of about 120 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 80° C.).

[0125] After the above-mentioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 80° C.) for about 3 hours.

[0126] After the reaction, the reaction solution was subjected to alkaline washing with an appropriate amount of 49.5 wt % sodium hydroxide aqueous solution at a constant temperature (about 70° C.) for about 1 hour. Thereafter, the water layer was removed.

[0127] Then, cyclohexanone is added to the organic solvent layer after the water layer is removed to recrystallize and remove the unreacted or unreacted polyphenylene ether at about 25° C. or below. Thereafter, methanol is added to precipitate the resin and dry it.

[0128] The number average molecular weight of the resin of Example 5 may be about 1,260 g / mole, the molecular weight distribution may be about 1.5, the resin hydroxyl equivalent may be about 360 g / eq, and the number of hydroxyl groups per molecule may be about 3.50. Furthermore, the total weight of the polymer single molecules with a molecular weight of more than 20,000 g / mole accounts for about 0.05 wt% of the total weight of the resin.

[0129] <Comparative Example 1>

[0130] About 600 g of toluene and about 100 g of commercially available polyphenylene ether (trade name: XYRON TM S202A), about 0.5 grams of tetramethylammonium chloride and about 8 grams of tetramethylbiphenol, and heated to 80°C to dissolve.

[0131] Then, about 19 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least six times) over a period of about 120 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 80° C.).

[0132] After the above-mentioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 80° C.) for about 3 hours.

[0133] After the reaction, the reaction solution was directly washed with water at a constant temperature (about 70° C.), and then the water layer was removed.

[0134] Then, methanol was added to the organic solvent layer after removing the water layer to precipitate the resin and dry it.

[0135] The number average molecular weight of the resin of <Comparative Example 1> may be about 1,815 g / mole, the molecular weight distribution may be about 4.50, the resin hydroxyl equivalent may be about 1,215 g / eq, and the number of hydroxyl groups per molecule may be about 1.5. Furthermore, the total weight of the polymer single molecule with a molecular weight of more than 20,000 g / mole accounts for about 6.5 wt% of the total weight of the resin.

[0136] <Comparative Example 2>

[0137] About 600 g of toluene and about 100 g of commercially available polyphenylene ether (trade name: XYRON TM S202A), about 0.5 grams of tetramethylammonium chloride and about 6 grams of tetramethylbiphenol, and heated to 80°C to dissolve.

[0138] Then, about 30 grams of about 75 wt % benzoyl peroxide is added dropwise (e.g., at least six times) over a period of about 120 minutes, with continuous stirring and a constant temperature (above about 70° C., such as about 70° C. to 80° C.).

[0139] After the above-mentioned dropwise addition is completed, the mixture is stirred continuously at a constant temperature (about 70° C. to 80° C.) for about 3 hours.

[0140] After the reaction, the reaction solution was directly washed with water at a constant temperature (about 70° C.), and then the water layer was removed.

[0141] Then, methanol was added to the organic solvent layer after removing the water layer to precipitate the resin and dry it.

[0142] The number average molecular weight of the resin of <Comparative Example 2> can be about 1,292 g / mole, the molecular weight distribution can be about 3.8, the resin hydroxyl equivalent can be about 685 g / eq, and the number of hydroxyl groups per molecule can be about 1.9. In addition, the total weight of the polymer single molecule with a molecular weight of more than 20,000 g / mole accounts for about 4.2 wt% of the total weight of the resin.

[0143] The corresponding adjustments and corresponding results of <Example 1> to <Example 5> and <Comparative Example 1> to <Comparative Example 5> are shown in [Table 1].

[0144] [Table 1]

[0145]

[0146]

[0147] <Evaluation method>

[0148] Specific molecular weight distribution ratio: The corresponding distribution ratio of a specific molecular weight can be estimated by the integral value of the corresponding molecular weight distribution curve. Taking the distribution ratio of molecular weight above 20,000 g / mol as an example, the integral value of the curve above 20,000 g / mol can be divided by the integral value of all molecular weight distribution curves to obtain the distribution ratio.

[0149] Number average molecular weight (Mn): The prepared modified polyphenylene ether resin was dissolved in tetrahydrofuran (THF) to prepare a test solution with a concentration of 1 wt %. Then, the test solution was measured for number average molecular weight by gel permeation chromatography (GPC).

[0150] Weight average molecular weight (Mw): The prepared modified polyphenylene ether resin was dissolved in tetrahydrofuran (THF) to prepare a test solution with a concentration of 1 wt %. Then, the test solution was measured for weight average molecular weight by gel permeation chromatography (GPC).

[0151] Polydispersity index (PDI): The measured weight average molecular weight is divided by the number average molecular weight (i.e., Mw / Mn) to obtain the polydispersity index (PDI). The smaller the PDI, the more concentrated the distribution of molecular weight is. Under the same or similar conditions of the initial reactants, catalysts, and their corresponding amounts, the smaller the PDI, the smaller the possibility of the corresponding side reaction, and the more concentrated the distribution of molecular weight is. Therefore, if the distribution of molecular weight is more moderate (i.e., the smaller the PDI), it can be expressed as more uniform in functional groups, morphology, and / or structure, and can be called a more uniform reaction / synthesis. In addition, if the distribution of molecular weight is more moderate (i.e., the smaller the PDI), the proportion of side reaction products (such as: larger polymer molecules formed by repolymerization) may be relatively small, so in terms of product application, it can also be more stable for subsequent processing or application, so that the subsequent processed products can have better quality or better yield.

[0152] Hydroxyl equivalent: can be calibrated by commonly used standards (such as, but not limited to, ISO 4629-2:2016, ASTM E222-10, GB / T 12008.3, CNS 6681).

[0153] Number of hydroxyl groups per molecule: can be converted from the corresponding hydroxyl equivalent and the corresponding molecular weight (such as the number average molecular weight).

[0154] As shown in [Table 1], compared with <Comparative Example 1> and <Comparative Example 2>, the modified polyphenylene ether resin of <Example 1> to <Example 5> (which may be a modified polyphenylene ether resin of one embodiment of the present invention) has a lower polydispersity index (PDI; i.e., Mw / Mn), and therefore, can be more stable for subsequent processing or application, so that the subsequent processed products can have better quality or better yield.

[0155] As shown in [Table 1], compared with <Example 1> to <Example 5>, the number average molecular weight of the resin of <Comparative Example 1> and <Comparative Example 2> (i.e., the modified polyphenylene ether resin not according to one embodiment of the present invention, which can be referred to as a non-modified polyphenylene ether resin) is comparable to that of <Example 1> to <Example 5>, but the proportion of molecules with a molecular weight of 20,000 g / mol or more is indeed high. This may be because it is difficult or impossible to precipitate the macromolecular polyphenylene ether because the corresponding alkali washing step is not performed. Therefore, the resin of <Comparative Example 1> and <Comparative Example 2> may be poor in subsequent applicability.

[0156] As shown in [Table 1], compared with <Comparative Example 1> and <Comparative Example 2>, the modified polyphenylene ether resins of <Example 1> to <Example 5> (which may be a modified polyphenylene ether resin of one embodiment of the present invention) have a higher number of hydroxyl groups per molecule. This may be because the method for manufacturing the modified polyphenylene ether resin of one embodiment of the present invention includes a corresponding alkali washing step, which can increase the number of hydroxyl groups per molecule.

[0157] <Examples and Comparative Examples of Application to Copper Foil Substrates>

[0158] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared by the above method.

[0159] In <Example 6> to <Example 10>, the modified polyphenylene ether used can be the modified polyphenylene ether obtained in <Example 1> to <Example 5>, respectively. In <Comparative Example 3>, the polyphenylene ether used can be a resin commonly used in the production of general copper foil substrates (such as: Sabic Company; resin model: SA-9000; that is, a modified polyphenylene ether resin other than one embodiment of the present invention can be referred to as a non-modified polyphenylene ether resin). In <Comparative Example 4>, the polyphenylene ether used can be the resin of <Comparative Example 1> (that is, a modified polyphenylene ether resin other than one embodiment of the present invention can be referred to as a non-modified polyphenylene ether resin).

[0160] In Examples 6 to 10 and Comparative Examples 3 and 4, the crosslinking agent used was triallyl isocyanurate sold by Mitsubishi Chemical Corporation.

[0161] In Examples 6 to 10 and Comparative Examples 3 and 4, the filler used was a silica filler sold by Sibelco under the trade name 525ARI series.

[0162] In Examples 6 to 10 and Comparative Examples 3 and 4, the crosslinking accelerator used was a product sold by Arkema SA under the trade name LuF series of peroxide formulated crosslinking accelerators.

[0163] In Examples 6 to 10 and Comparative Examples 3 and 4, the flame retardant used was a phosphorus-based flame retardant sold by Otsuka Chemical Co., Ltd. under the trade name SPB-100.

[0164] In <Example 6> to <Example 10> and <Comparative Example 3> and <Comparative Example 4>, about 53 parts by weight (calculated as: 53wt%) of a resin composition (including one of the aforementioned modified polyphenylene ether resin or non-modified polyphenylene ether resin, a cross-linking agent, a filler, a cross-linking accelerator and a flame retardant) is mixed with about 47% by weight (calculated as: 47wt%) of a solvent (toluene / butanone co-solvent) to serve as the corresponding resin varnish composition for preparing a copper foil substrate.

[0165] <Example 6>

[0166] The resin of Example 1 was olefinated with methacrylic anhydride.

[0167] Specifically, about 100 grams of toluene, about 100 grams of the resin of Example 1, about 14.7 grams of methacrylic anhydride and about 8.9 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 85° C. for about 4 hours.

[0168] After the reaction, methanol was added to precipitate and wash the resin.

[0169] The cleaned resin was dried and the acid value was measured to be about 1.44 mgKOH / g, the OH value was measured to have a residual hydroxyl group of about 0.5 mgKOH / g, the number average molecular weight was about 2,840 g / mol, and the molecular weight distribution was about 1.45.

[0170] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared by the above-mentioned method. Then, evaluation was performed.

[0171] Specifically, in Example 6, based on the total weight of the resin composition of about 100 parts by weight, the resin composition includes about 40 parts by weight (40 wt%) of the olefinized resin of Example 1, about 15 parts by weight (15 wt%), about 10 parts by weight (10 wt%) of filler, about 1 part by weight (1 wt%) of cross-linking accelerator, and about 10 parts by weight (10 wt%) of flame retardant. In addition, about 53 parts by weight (53 wt%) of the resin composition is mixed with about 47 wt% (47 wt%) of solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing the copper foil substrate in Example 6.

[0172] <Example 7>

[0173] The resin of Example 2 was olefinated with methacrylic anhydride.

[0174] Specifically, about 100 grams of toluene, about 100 grams of <Example 2> resin, about 18.7 grams of methacrylic anhydride and about 11.5 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 90° C. for about 5 hours.

[0175] After the reaction, methanol was added to precipitate and wash the resin.

[0176] The cleaned resin was dried and the acid value was measured to be about 1.34 mgKOH / g, the OH value was measured to have a residual hydroxyl group of about 0.1 mg KOH / g, the number average molecular weight was about 2,460 g / mole, and the molecular weight distribution was about 1.41.

[0177] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared in the same manner as in <Example 6> and evaluated.

[0178] Specifically, in Example 7, based on the total weight of the resin composition of about 100 parts by weight, the resin composition includes about 40 parts by weight (40 wt%) of the olefinized resin of Example 2, about 15 parts by weight (15 wt%) of the filler, about 10 parts by weight (10 wt%) of the cross-linking accelerator, and about 10 parts by weight (10 wt%) of the flame retardant. In addition, about 53 parts by weight (53 wt%) of the resin composition is mixed with about 47 wt% (47 wt%) of the solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing the copper foil substrate in Example 7.

[0179] <Example 8>

[0180] The resin of Example 3 was olefinated with methacrylic anhydride.

[0181] Specifically, about 100 grams of toluene, about 100 grams of <Example 3> resin, about 27.2 grams of methacrylic anhydride and about 16.6 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 95° C. for about 6 hours.

[0182] After the reaction, methanol was added to precipitate and wash the resin.

[0183] The cleaned resin was dried and the acid value was measured to be about 1.2 mgKOH / g. The OH value titration showed that the residual hydroxyl group was about 0.7 mgKOH / g, the number average molecular weight was about 2,392 g / mole, and the molecular weight distribution was about 1.43.

[0184] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared in the same manner as in <Example 6> and evaluated.

[0185] Specifically, in Example 8, based on the total weight of the resin composition of about 100 parts by weight, the resin composition includes about 40 parts by weight (40 wt%) of the olefinized resin of Example 3, about 15 parts by weight (15 wt%) of filler, about 10 parts by weight (10 wt%) of cross-linking accelerator, and about 10 parts by weight (10 wt%) of flame retardant. In addition, about 53 parts by weight (53 wt%) of the resin composition is mixed with about 47 wt% (47 wt%) of solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing the copper foil substrate in Example 8.

[0186] <Example 9>

[0187] The resin of Example 4 was olefinated with methacrylic anhydride.

[0188] Specifically, about 100 grams of toluene, about 100 grams of <Example 4> resin, about 27.6 grams of methacrylic anhydride and about 15.5 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 85° C. for about 6 hours.

[0189] After the reaction, methanol was added to precipitate and wash the resin.

[0190] The cleaned resin was dried and the acid value was measured to be about 1.2 mgKOH / g. The OH value titration showed that the residual hydroxyl group was about 0.2 mgKOH / g, the number average molecular weight was about 1,955 g / mole, and the molecular weight distribution was about 1.45.

[0191] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared in the same manner as in <Example 6> and evaluated.

[0192] Specifically, in Example 9, based on the total weight of the resin composition of about 100 parts by weight, the resin composition includes about 40 parts by weight (40 wt%) of the olefinized resin of Example 4, about 15 parts by weight (15 wt%) of the filler, about 10 parts by weight (10 wt%) of the cross-linking accelerator, and about 10 parts by weight (10 wt%) of the flame retardant. In addition, about 53 parts by weight (53 wt%) of the resin composition is mixed with about 47 wt% (47 wt%) of the solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing the copper foil substrate in Example 9.

[0193] <Example 10>

[0194] The resin of Example 5 was olefinated with methacrylic anhydride.

[0195] Specifically, about 100 grams of toluene, about 100 grams of <Example 5> resin, about 51.3 grams of methacrylic anhydride and about 27.1 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 85° C. for about 4 hours.

[0196] After the reaction, methanol was added to precipitate and wash the resin.

[0197] The cleaned resin was dried and the acid value was measured to be about 1.5 mgKOH / g. The OH value titration showed that the residual hydroxyl group was about 0.1 mgKOH / g, the number average molecular weight was about 1,417 g / mole, and the molecular weight distribution was about 1.45.

[0198] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared in the same manner as in <Example 6> and evaluated.

[0199] Specifically, in Example 10, based on the total weight of the resin composition of about 100 parts by weight, the resin composition includes about 40 parts by weight (40 wt%) of the olefinized resin of Example 5, about 15 parts by weight (15 wt%) of the filler, about 10 parts by weight (10 wt%) of the cross-linking accelerator, and about 10 parts by weight (10 wt%) of the flame retardant. In addition, about 53 parts by weight (53 wt%) of the resin composition is mixed with about 47 wt% (47 wt%) of the solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing the copper foil substrate in Example 10.

[0200] <Comparative Example 3>

[0201] A resin of model number SA-9000 (manufactured by Sabic Corporation) was olefinated with methacrylic anhydride.

[0202] Specifically, about 100 grams of toluene, about 100 grams of the resin of Comparative Example 1, about 15.2 grams of methacrylic anhydride and about 8.5 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 85° C. for about 4 hours.

[0203] After the reaction, methanol was added to precipitate and wash the resin, and then centrifuged using toluene as solvent to remove insoluble products (including the corresponding resin).

[0204] The product (which may include the corresponding resin) is dried and the acid value is measured to be about 2.2 mgKOH / g. The OH value titration shows that the residual hydroxyl group is about 0.1 mg KOH / g, the number average molecular weight is about 1452 g / mole, and the molecular weight distribution is about 1.8.

[0205] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared in the same manner as in <Example 6> and evaluated.

[0206] Specifically, in <Comparative Example 3>, based on the total weight of the resin composition being about 100 parts by weight, the resin composition includes about 40 parts by weight (can be calculated as: 40wt%) of olefinized SA-9000 resin, about 15 parts by weight (can be calculated as: 15wt%) of filler, about 10 parts by weight (can be calculated as: 10wt%) of cross-linking accelerator, and about 10 parts by weight (can be calculated as: 10wt%) of flame retardant. In addition, about 53 parts by weight (can be calculated as: 53wt%) of the resin composition is mixed with about 47% by weight (can be calculated as: 47wt%) of solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing the copper foil substrate in <Comparative Example 3>.

[0207] <Comparative Example 4>

[0208] The resin of <Comparative Example 1> was olefinated with methacrylic anhydride.

[0209] Specifically, about 100 grams of toluene, about 100 grams of the resin of Comparative Example 4, about 15.2 grams of methacrylic anhydride and about 8.5 grams of 4-dimethylaminopyridine (DMAP) were added to a reaction container, and dry nitrogen was filled in the reaction container, and heated to about 85° C. for about 4 hours.

[0210] After the reaction, methanol was added to precipitate and wash the resin, and then centrifuged using toluene as solvent to remove insoluble products (including the corresponding resin).

[0211] The product (which may include the corresponding resin) is dried and the acid value is measured to be about 2.2 mgKOH / g. The OH value titration shows that the residual hydroxyl group is about 0.1 mg KOH / g, the number average molecular weight is about 1452 g / mole, and the molecular weight distribution is about 1.8.

[0212] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared in the same manner as in <Example 6> and evaluated.

[0213] Specifically, in <Comparative Example 4>, based on the total weight of the resin composition being about 100 parts by weight, the resin composition includes about 40 parts by weight (can be calculated as: 40wt%) of the olefinized resin of <Comparative Example 1>, about 15 parts by weight (can be calculated as: 15wt%), about 10 parts by weight (can be calculated as: 10wt%) of filler, about 1 part by weight (can be calculated as: 1wt%) of cross-linking accelerator, and about 10 parts by weight (can be calculated as: 10wt%) of flame retardant. In addition, about 53 parts by weight (can be calculated as: 53wt%) of the resin composition is mixed with about 47% by weight (can be calculated as: 47wt%) of a solvent (toluene / methyl ethyl ketone co-solvent) to serve as the resin varnish composition for preparing a copper foil substrate in <Comparative Example 3>.

[0214] <Application examples and comparative examples of copper foil substrates>

[0215] The resin varnish composition was mixed in the formulation ratio shown in [Table 2], and a copper foil substrate was prepared by the above method.

[0216] [Table 2]

[0217]

[0218] <Evaluation method>

[0219] a. Dynamic viscosity test

[0220] The corresponding evaluation was conducted on a prepreg of 2116 glass fiber cloth with a resin content (RC) of 53% (recorded as: 2116RC53%). The method is: the aforementioned prepreg is kneaded to produce powder, and about 0.45 grams of the powder is placed in a commonly available rheometer (such as: Waters (TA Instruments, Inc.) or Hitachi (HITACHI)) for dynamic viscosity measurement. The measurement conditions are as follows: the heating rate is about 2.5°C / min, the measurement temperature range is 50°C to 180°C, the lowest viscosity value (unit: Pa.second (Pa·s)) is taken and recorded, and the lowest point temperature with about the lowest viscosity value (recorded as: lowest point; unit: ℃) and the corresponding temperature range (recorded as: Width; unit: ℃) are recorded. In addition, the temperature range (denoted as: Width; unit: °C) represents the corresponding temperature range in which the viscosity of the resin composition is below 10000 Pa·s. By comparing the temperature range, the operability difference of the corresponding resin can be expressed. For example, if the temperature range is larger, the operability is better.

[0221] b. Water absorption

[0222] Place a 5cm×5cm square test piece in an oven at about 105℃ for an appropriate measurement time (e.g., about 2 hours), and then place the test piece in a pressure cooker. The environmental conditions in the pressure cooker are about 2atm×120℃. After about 120 minutes in the pressure cooker, record the weight difference of the test piece before and after the pressure cooker ÷ the initial weight of the test piece × 100% to get the water absorption rate.

[0223] c. Heat resistance

[0224] The test method is to immerse the above-mentioned pressure cooker test piece in a 288±5℃ soldering furnace and observe. Record the time required for the test piece to explode and delaminate. Generally speaking, if there is no explosion and delamination within 60 minutes, it can pass the heat resistance test.

[0225] d. Peel strength

[0226] In a similar manner to the above, the films made from the resin compositions of the above formulations were tested for peel strength using a universal tensile machine according to IPC-TM-650, Method 2.4.8.

[0227] e. Dielectric constant (Dk)

[0228] Dielectric constant test: The test method is to bake a 5cm×5cm square test piece of copper foil substrate with the copper foil removed in an oven at about 105℃ for about 2 hours, measure the thickness with a thickness meter, and then clamp the test piece into an impedance analyzer (Agilent E4991A), measure the dielectric constant Dk data at 3 points and take the average value.

[0229] f. Dielectric loss (dissipation factor, Df)

[0230] Dielectric loss (Dissipation factor) test: The test method is to bake a 5cm×5cm square test piece of the copper foil substrate with the ketone foil removed in an oven at about 105℃ for about 2 hours, measure the thickness with a thickness meter, and then clamp the test piece into an impedance analyzer (Agilent E4991A), measure the dissipation factor Df data at 3 points and take the average value.

[0231] g. Glass transition temperature (Tg)

[0232] Similar to the above method, the glass transition temperature (Tg) of the films made of the resin compositions of the above formulations was measured by a dynamic mechanical analyzer (DMA).

[0233] <Evaluation Results>

[0234] From the experimental results in [Table 2], it can be seen that the modified polyphenylene ether resin of one embodiment of the present invention can be used to manufacture copper foil substrates. Moreover, the electrical properties and / or glass transition temperature of the manufactured copper foil substrates are comparable to or better than those of conventional resins (e.g., polyphenylene ether resins used in the manufacture of general copper foil substrates).

[0235] In addition, Dk and Df can still meet the dielectric level of general copper foil substrates (eg, Df is a very low loss level of 0.0030 to 0.0065).

[0236] Moreover, compared with the use of conventional resins (eg, polyphenylene ether resins used in the manufacture of common copper foil substrates), the other properties are all equivalent to or within the corresponding standard specifications.

[0237] Based on the above, compared with the commercially available resin for manufacturing copper foil substrates, the modified polyphenylene ether resin of one embodiment of the present invention can be prepared more simply. In addition, the modified polyphenylene ether resin of one embodiment of the present invention can be applied to the manufacture of copper foil substrates, and / or the copper foil substrates manufactured using the modified polyphenylene ether resin can meet the commonly used specifications.

[0238] Furthermore, since the modified polyphenylene ether resin of one embodiment of the present invention can be prepared by adjusting the preparation method and / or the corresponding proportion, the corresponding resin composition applied to the copper foil substrate can meet the customized specification requirements. For example, the glass transition temperature can be changed accordingly by the corresponding number of hydroxyl groups (e.g., the number of hydroxyl groups per molecule and the glass transition temperature are basically positively correlated). For example, the smaller the molecular weight, the higher the fluidity may be. For another example, the higher the molecular weight, the higher the corresponding peel strength may be.

[0239] [Practicality]

[0240] In addition, the modified polyphenylene ether resin of the aforementioned embodiment of the present invention can be directly or indirectly applied to a copper foil substrate, and can be further processed to become other electronic components or electronic products (such as circuit boards or copper foil substrates) for civilian, industrial or suitable applications.

[0241] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a modified polyphenylene ether resin, characterized in that: include: Providing unmodified polyphenylene ether; reacting the unmodified polyphenylene ether with a polyphenolic compound and a free radical initiator to obtain a corresponding product; as well as The product is purified, alkali washed and solvent recrystallized to obtain modified polyphenylene ether resin.

2. The method for preparing a modified polyphenylene ether resin according to claim 1, characterized in that: The unmodified polyphenylene ether includes poly(2,6-dimethyl-1,4-phenylene ether).

3. The method for preparing a modified polyphenylene ether resin according to claim 1, characterized in that: The equivalent weight of the free radical initiator is about 0.05 to about 2 times the phenol equivalent weight of the polyphenolic compound.

4. The method for preparing a modified polyphenylene ether resin according to claim 1, characterized in that: The process of reacting the unmodified polyphenylene ether with the polyphenol compound and the free radical initiator further includes adding a catalyst.

5. A modified polyphenylene ether resin, characterized in that: It has a structure represented by the following [Formula 1]: [Formula 1], Wherein in [Formula 1]: k is an integer greater than or equal to 0; i, i', j, j' are the same or different from each other; i and j are integers of 0 to 200; and i' and j' are integers of 1 to 200; The value of i+i'+j+j'+k is between 2 and 400; R1 to R8 may be the same or different from each other and are each selected from a hydrogen group or an alkyl group having C1 to C6; P1 to P4 may be the same or different from each other and are each selected from a single bond or a keto group; Q1 to Q4 may be the same or different from each other and are each selected from a phenyl group, a phenylvinyl group, a phenylethynyl group, an ethynyl group, a vinyl group, a methylvinyl group, a naphthyl group or hydrogen; and X is a linking group selected from a single bond or the following:

6. The modified polyphenylene ether resin according to claim 5, characterized in that: Prepared by the preparation method of modified polyphenylene ether resin according to claim 1.

7. The modified polyphenylene ether resin according to claim 5, characterized in that: Features include: The number average molecular weight is between 500 g / mole and 4,000 g / mole; The molecular weight distribution is less than or equal to 2.5; and Based on the total weight of the modified polyphenylene ether resin, the total weight of components with a molecular weight greater than 20,000 g / mole accounts for less than 1.5 wt%.

8. The modified polyphenylene ether resin according to claim 5, characterized in that: The average number of hydroxyl groups per molecule is greater than or equal to 2.

2.

9. A resin composition, characterized in that: include: The modified polyphenylene ether resin as claimed in claim 5.

10. An electronic component, characterized in that: include: A film layer formed from the resin composition as claimed in claim 9.